Study Analysis Of Infectious Diseases And Level Of Protein Consumption With Nutritional Status Of Sanleo Village, East Malaka District, District Malaka, East Nusa Tenggara - Octavianus Subani Amfotis; Nurwijayanti (Universitas STRADA Indonesia, 2023)
According to UNICEF, there are two causes that can affect the nutritional status of children under five, namely direct causes and indirect causes. There are two direct causes, namely nutritional intake and infectious diseases. Nutritional intake can be caused by an unbalanced intake of food consumed or food that does not meet the requered nutritional elements. Meanwhile, infection causes damage to several functions of the body’s organs so that they cannot absorb food substances properly. The purpose of this study was to analyze the relationship between the incidence of infectious diseases and the level of protein consumption with the nutritional status of toddlers aged 24-59 months in Sanleo Village, East Malaka District, Malaka District, East Nusa Tenggara. Analytical research method with cross sectional approach. The number of samples was 92 respondents using simple random sampling technique. Using Chi-square data analysis test. The result of study based on bivariate analysis that were not related to the nutritional status of toddlers 24-59 months in Sanleo village, East Malaka sub-District, Malaka District, East Nusa Tenggara, were infectious diaseases with a p value 0,35 > 0,05, while those related to nutritional status were the level of protein consumption with a P value (0,00) < α (0,05).The variable related to nutritional status is the level protein consumption. Research advice, the community needs to increase protein consumption for toddlers so that the nutritional status of toddlers can be maintained.